Aref Jeribi and Bilel Krichen; Nonlinear functional analysis in Banach spaces and Banach algebras. Fixed point theory under weak topology for nonlinear operators and block operator matrices with applications, Monographs and Research Notes in Mathematics, - PETRUȘEL, Adrian (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
The book is dedicated to fixed point theory in the weak topology setting and its applications to block operator matrices. The book discusses various aspects of fixed point theory in Banach spaces and Banach algebras with nice applications to Mathematical Physics and Mathematical Biology. The structure of the book is the following: two main parts: I. Fixed Point Theory, II. Applications to Mathematical Physics and Biology, preceded by a Preface and followed by a consistent References list with 154 titles.